Sosialisasi Efektifitas Penggunaan Pewarna Alternatif Preparat Permanen Telur Nematoda Kolon Menggunakan Pewarna Rhodamin B - Saadah Siregar; Vincentia Ade Rizky; Asvia Rahayu; Visensius Krisdianilo (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
Staining is one way to do research to identify eggworms. The dyeing technique explains the material and description of the  worm egg under the microscope and helps to distinguish it from the surrounding feces. A widely used method for staining  histological tissue with hematoxylin and eosin. A commonly used stain for the above colon nematode examination  is eosin stain. Rhodamine B dye is used instead of eosin dye to add a reference dye. The method used is experimental and uses eosin-controlled rhodamine B concentration ratios of 0.5%, 1%, 1.5%, and 2% to 3%. The  worm egg morphology is clearly visible from the outer layer to the inner layer, the  field of view of the rhodamine B dye is clearly visible, and the color contrast of the egg  is also clearly visible. From the research conducted, it can be concluded that Rhodamine B can be used as an alternative to the dye eosin. After the seminar, participants in the dedication activity realized that dye Rhodamine B  was used instead of dye eosin.Keywords: intestinal nematode egg, hematoxylin-eosin, rhodamine B